Architecture for Healthcare Facilities (International Journal of Innovative Research in Engineering & Management, 2022)
The development of any nation majorly  depends on the well-being of its citizens. As the cliché goes  ‘Health is wealth’, The most significant luxury that one, as  well as any nation, can hold is good health. A country’s  economic and social growth broadly depends on the  sustainability and viability of its healthcare sector. Any  country around the world cannot maintain steady economic  growth in the absence of an adequate healthcare system. The  study tries to understand the elements, philosophies, and  spatial as well as the sensorial aspects of healthcare  architecture. The focus here is to decode the importance of  healthcare in humans through the study of spatial design in a  healthcare facility. The focus here is to understand the role  of spatial elements of Architectural design in the process of  healing the healthcare condition of a human in a hospital.  Also, the study tries to understand the impact of various  architectural elements on the psychology of a patient.
Keywords: Architecture; Health; Facilities; Patient; Spatial